The Implementation of Canva-Based Barcode Learning Media to Improve Learning Outcomes on Local Wisdom Material Using the PJBL Model at SMA Negeri 1 Mojotengah, Wonosobo - Erfi Yana Eka Susanti; Beny Wijanarko; Sriyanto Sriyanto (UM Purwokerto Press, 2025)
This study aims to analyze the effectiveness of using barcode-based instructional media through the Canva application in improving students' learning outcomes on local wisdom material at SMA Negeri 1 Mojotengah. The research employs a descriptive quantitative approach with the Project-Based Learning (PJBL) method. By utilizing interactive instructional media, students can access information more flexibly and actively engage in the learning process. The findings indicate that the implementation of barcode-based instructional media using Canva enhances students' understanding and appreciation of local wisdom while promoting more innovative and collaborative learning. Thus, this model effectively supports the Merdeka Belajar (Independent Learning) concept and can serve as an alternative in developing technology-based teaching methods.